Proximate Composition of Aframomum melegueta Seeds, Garcinia kola Seeds and Growth Performance of Broiler Chicks Treated with Powders from These Seeds - Ibekwe, H.A.; Orok, E.E. (International Journal of Poultry Science, 2010)
This study was designed to evaluate the nutritive value of powdered seeds of two important medicinal plants in West Africa. The proximate analysis of these two set of seeds were carried out prior to bird’s treatment so as to throw more light on their nutritional potential. A total of 18 broiler chicks of Anak 2000 strain were used in this study. Treatment one (control) received 0% inclusion of these seeds whereas treatment two and three received 10% Aframomum melegueta and Garcinia kola seeds respectively. The treatment was terminated after 5 weeks and live body mass of birds taken. The result obtained showed a non-significant (p>0.05) reduction in the body mass of broiler chicks reflecting their poor proximate composition. This finding may be an indication that these seeds should not be used as non-conventional feed source for poultry production. It however lends credence to their medicinal uses without compromising the body mass of birds.